Towards a conceptualised belief-action-outcome model for enhanced non-financial reporting: A systematic and integrative review - Cristina Alexandrina Ştefănescu (Revista de Contabilidad: Spanish Accounting Review)
This study aims to advance knowledge in the field of non-financial reporting (NFR) research by examining how academic and business insights into the qualitative dimensions of NFR have shaped the requirements of the new CSRD (Corporate Sustainability Reporting Directive) and its desired outcome of increased transparency. The research design enriches scholarship by combining the methodologies of systematic and integrative literature review, and lays the foundations for a conceptual model based on a literature taxonomy to support further research. This study represents the first attempt to empirically address the links between academics, business practitioners and regulators by integrating them into an original conceptual model based on the Belief-Action-Outcome framework. It highlights the interconnectedness between the cognitive, attitudinal and behavioural dimensions of the tripartite relationship derived from the literature taxonomy using partial least squares structural equation modelling (PLS-SEM). The results reveal meaningful relationships between the three perspectives, as hypothesised, which shed light on the valuable contributions of academics to the NFR regulatory process. Specifically, academic insights into the qualitative dimensions of NFRs positively influenced the requirements of CSRD and its outcome of increased transparency. In addition, practitioners' attitudes expressed through public consultations on NFRD reinforced this outcome through their positive moderating effect. The study is relevant to regulators, practitioners and academics interested in engaging in challenging debates about sustainability reporting. It catalyzes understanding the link between academic and real-world evidence, supporting regulatory progress, and leading to a virtuous cycle of value creation and meaningful communication.